The cognitive chronometric architecture of reading aloud: semantic and lexical effects on naming onset and duration - Gould, Layla; Cummine, Jacqueline; Borowsky, Ron (Frontiers in Human Neuroscience, 2012)
We examined onset reaction time (RT) in a word naming task using an additive factors method. The pattern of additive and overadditive joint effects on RT among Instructions (INST: name all, name words), Word Frequency (WF: log10HAL), Semantic Neighbourhood Density (SND: Inverse Ncount), and Word Type (WT: regular, exception) supported a cognitive chronometric architecture consisting of at least two cascaded stages of processing, with the orthographic lexical system as the locus of the INST x WF and the INST x SND interactions, and the phonological output system as the locus of the WF x WT and the SND x WT interactions. Additivity between INST and WT supports the notion that these variables affect separable systems, and a WF x SND interaction supports a common locus of their effects. These results support stage-like/cascaded processing models over parallel processing models of basic reading. We also examined response duration (RD) in these data by recording and hand-marking vocal responses, which provides evidence that basic reading processes are ongoing even after the initiation of a vocal response, and supports the notion that the more lexically a word is read, the shorter the RD. As such, the effects of WT and INST on RD were opposite to their effects on RT, however the effects of WF and SND on RD were in the same direction as their effects on RT. Given the combination of consistent and dissociating effects between RT and RD, these results provide new challenges to all models of basic reading processes.